VEGETATIVE DYSTONIA SYNDROME AS ETIOLOGY ULCER DISEASE (LITERATURE REVIEW) - Kadirov Bekhruzbek Saidovich (World Scientific Research Journal, 2025)
Resume. The article discusses the nosology of gastric ulcer and duodenal ulcer, pathogenetic mechanisms of their occurrence, pathomechanisms of their connection with the syndrome of vegetative dystonia, the main cause of which is the endogenous factor of the disease development - dysfunction of the autonomic nervous system. The main causative agent of the disease, Helicobacter pylori, was not left without attention..